Monetary policy and financial (in)stability - Adam Koronowski (Contemporary Economics, 2010)
This paper presents how monetary policy, restricted only by price stability, may easily become propitious to asset inflation and eventually to a financial crisis. This risk is particularly high when the financial system lacks proper regulation and effective supervision. Hasty liberalization, negligence of official oversight and Greenspan doctrine which refuted any activist policy promoting financial stability characterized Fed's monetary policy under the former Fed's governor. The paper also analyses another aspect of the linkages between monetary policy and financial crises - monetary policy reaction to financial crises. It is not surprising that it consists of cutting interest rates and bail-out of insolvent, systemically important financial institutions. Such policy, especially when run too long and changed too abruptly, not only creates moral hazardsbut it also sets the stage for another search for yield and build-up of another speculative bubble. As a result, monetary policy becomes asymmetric and pro-cyclical. Fed's reaction to the recent crisis seems to be very much in line with this pattern typical of Fed's policy in the past. However, this time the scale of flooding the economy with liquidity and - as a consequence - the risks of future major imbalances in the financial system are unprecedented. A general conclusion of the paper says that there can't be a sound financial and economic system unless money itself is a scarce resource. However trivial this statement is, monetary policy of some central banks seems to miss the point.
Keywords: 330